Solve -4*q - 2*g = -26, 5*q - 5 = 3*g - 0 for q.

4

Solve 13*f = 16*f - 5*b + 1, 31 = -5*f + b for f.

-7

Solve 12 = 3*u, -11 = -3*k - u + 2*u for k.

5

Solve g - 1 = 2*y, g - 5*y + 6 - 1 = 0 for g.

5

Solve 0 = -5*m + y - 7, -2*m + 0*y + 2 = 2*y for m.

-1

Solve -4*a = -4*u + 32, -6*a - 12 = -2*a for u.

5

Solve -3*q - 9*n - 34 = -4*n, 5*q + n - 2 = 0 for q.

2

Solve -10 = 3*o + a, 3*a = o - 2*a + 30 for o.

-5

Solve -3*j + 17*x - 22*x = 21, -5 = j + x for j.

-2

Solve 5*i = -3*y - 28, -3*y - 15 = 2*i + 2*y for i.

-5